Implementasi Kebijakan Pembangunan Infrastruktur Jalan Lingkar Pesisir Tanjungpinang - Stevy Indah Pratama; Muhammad Randianto; Aswandi Aswandi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In terms of public welfare, the Republic of Indonesia makes many policies, especially on road infrastructure development policies. One of the policies is the coastal ring road infrastructure development policy contained in the Strategic Plan (RENSTRA) of the Office of Public Works, Spatial Planning and Land Affairs, which aims to improve the implementation of effective, clean and reliable infrastructure development and is supported by qualified human resources. high performance. Not only that, infrastructure development is a strategy from the government to serve as a foundation in building new economic areas that are able to have a positive impact on the surrounding community. In 2018 the Provincial Government of the Riau Islands together with the Provincial DPRD officially claimed a budget of 428 billion in the construction of the Gurindam 12 mega project for structuring coastal areas which sourced funds from the Riau Islands Province APBD. Coastal communities really need functioning infrastructure, especially roads, to carry out their economic activities. The seaside is one of the coastal areas that has a lot of economic activity which really needs adequate infrastructure. Because of the several things above, researchers are interested in researching problems related to this. The purpose of this research is to see how policy implementation measures the success or failure of a policy is largely determined by the implementation of the policy; plan success 20%, implementation is 60% remaining 20% how do we control the implementation using qualitative research methods. The construction of ring road infrastructure in the city of Tanjungpinang which was built by the government has positive and negative impacts. The positive impact of this development can limit the flow of waves and wind when a storm occurs, while the negative impact is reduced catch (shrimp) which previously could be 4 kg per day/night now only 2 kg per day/night.